Information searching and seeking behaviour of the farmers for cattle disease management: A case study of rural Bangladesh (Indian Journal of Animal Production and Management, 2024)
Livestock sector, especially cattle, is a large contributor to the national economy and a vital nutrition source  for millions of people in Bangladesh. Majority of the rural farmers are involved in the homestead cattle rearing  along with their main crop cultivation and many of them are using commercial cattle rearing as their main  occupation. While rearing cattle, it is usual for them to encounter different cattle diseases and they, to their  best of the abilities, look for information to manage those diseases. This study, thus, was undertaken to  explore the information search and seeking behavior of the cattle farmers for cattle disease management.  The study was based on Wilson’s nested model of information behavior. It was carried out in Madargonj  and Sharishabari sub-district of Jamalpur district of Bangladesh. One hundred farmers were interviewed  using a semi-structured questionnaire. Appropriate scales were used to measure the concerned variables.  Descriptive analysis was done to see the outcome of the study. It was observed that farmers faced low  to moderate disease infestation in their cattle and worm infestation being the most frequent one. They,  besides, search for information from less to a moderate degree. Farmers tend to approach local sources  like experienced farmers, neighbours and friends, large local farmers etc. for information. They seek other  information sources only when something is beyond the capabilities of local sources like vaccination or  medicine prescription for disease management. The lack of field-level livestock extension worker seems  to be one of the major factors that break the information flow between farmers and Government agencies.  The lack of Government campaigns related to livestock extension is also contributing for not influencing  farmers to look for specialized and professional information sources. Government agencies and other  relevant organizations working in livestock extension field should take initiatives to reach to the farmers and  spread the importance to look for diversified sources to have professional and authentic cattle health-related  information. Besides, it seems to be a timely need to recruit more field-level livestock extension workers in  Bangladesh so that farmers can easily access better professional opinion on cattle disease management.
Keywords: Economy; Extension workers; Information; Local; Vaccination; SHONIA SHEHELISHONIA SHEHELI